Childhood socioeconomic status and genetic risk for poorer cognition in later life. (September 2018) - Moorman, Sara M.; Carr, Kyle; Greenfield, Emily A.
Abstract: The ε4 allele of the APOE gene is associated with poorer cognition in later life. This study aimed to advance understanding of how environments potentially moderate this genetic risk by focusing on childhood socioeconomic status (SES). Previous research across diverse national contexts has found that older adults from higher-SES families in childhood demonstrate better cognitive functioning than their lower-SES counterparts. Nevertheless, few studies have examined whether higher childhood SES might also promote later life cognition by mitigating the effects of ε4 carrier status. To address this gap, we used data from 3017 participants in the Wisconsin Longitudinal Study, which has followed a random sample of people who graduated from Wisconsin high schools in 1957. Childhood SES included parents' educational attainment, father's occupational status, and household income in adolescence. We constructed measures of memory and of language/executive functioning using scores from neurocognitive tests administered when participants were approximately ages 65 and 72. APOE ε4 status was measured through saliva samples. Results from cross-controlled multilevel models indicated that APOE ε4 status—and not childhood SES—independently predicted memory, whereas childhood SES—and not APOE ε4 status—independently predicted language/executive functioning. Moreover, a statistical interaction between APOE ε4 status and childhood SES for memory indicated that at baseline, higher childhood SES protected against the risk of APOE ε4 status, whereas lower childhood SES exacerbated the risk of APOE ε4 status. However, by follow-up, these moderating effects dissipated, and APOE ε4 status alone was associated with memory. We interpret these results in light of theorizing on differential susceptibility for poorer cognition across the life course. Highlights: Higher childhood SES predicted better language/executive function in older adulthood. APOE ε4 carrier status was unrelated to language/executive function. For memory, APOE ε4 carriers had differential susceptibility to childhood SES. Differential susceptibility dissipated with age.